The impact of dividends withholding tax reclaim processes on foreign investment returns: exploring the complexities and challenges - Maxongo, Vuyowethu Tony (University of the Witwatersrand, Johannesburg, 2024)
Investors continually seek opportunities for portfolio growth, long-term capital appreciation, return on investments, and/or diversification in their investment portfolio. This investor outlook often leads investors to invest in shares outside of their local stock exchange or invest in dual- listed shares. With advances in technology, cross-border transactions have increased, making it easier for resident investors to purchase shares in foreign markets and for non-resident investors to purchase shares in local markets. Withholding taxes are taxes which are withheld for payments of dividends to shareholders. Dividends withholding taxes, however, have the potential to reduce an investor’s return on investment due to the complexities involved in the process of claiming a refund in instances where dividends tax has been incorrectly withheld. The complexities in the refund process often include the time-consuming process of submitting appropriate documentation to support the claim, the long timeframe for processing refunds, forfeiture of the refund as a result of failing to claim within the specified timeframe, burdensome administrative procedure to be followed, language barriers in claiming a refund in a foreign jurisdiction, unfamiliar legal requirements and the potential for tax authorities to conduct audits and reviews to verify the legitimacy of the refund claim. This research report examines the complexities of dividend withholding tax reclaim processes and the impact on foreign investment returns. To achieve this aim, the research report is grounded in a systematic literature review approach. This approach involves a rigorous analytical methodology that aggregates, interprets and synthesises data extracted from the literature in applicable legislation, book chapters, journal articles and case law. The report analyses a sample of two double tax agreements concluded by South Africa. The first tax treaty is with the Netherlands (SARS 2009), a developed country, and the second tax treaty is with Namibia (SARS 1999), a developing country. The findings of this report indicate that the complexities of the dividend withholding tax reclaim processes significantly impact foreign investors’ returns on investment. The report highlights the need for greater transparency and consistency in these processes, including the reduction of documentation requirements and the development of efficient electronic systems. The report's implications are essential for policymakers, financial institutions, and foreign investors, emphasising the importance of improving the efficiency and effectiveness of dividend withholding tax reclaim processes to support cross-border investments
A research report submitted in fulfillment of the requirements for the Master of Commerce, In the Faculty of Faculty of Commerce, Law and Management, School of Accountancy, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Beneficial owner; contributed tax capital; dividend; dividend in specie; dividends tax; dividend withholding tax; Double Tax Agreements (DTA); Income Tax Act 58 of 1962; return on investment; Organization for Economic Cooperation and Development (OECD); withholding tax; SDG-8: Decent work and economic growth